Optimization and network performance evaluation of beamforming and dynamic DTX techniques in 5G/6G systems - Santana Júnior, Ezequias Márcio Silva de (2022)
SANTANA JÚNIOR, Ezequias Márcio Silva de. Optimization and network performance evaluation of beamforming and dynamic DTX techniques in 5G/6G systems. 2022. 55 f. Dissertação (Mestrado em Engenharia de Teleinformática) – Centro de Tecnologia, Universidade Federal do Ceará, Fortaleza, 2022.